2014
DOI: 10.1016/j.pain.2014.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of single nucleotide polymorphisms and copy number variants in fibromyalgia suggest a role for the central nervous system

Abstract: Fibromyalgia (FM) is a highly disabling syndrome defined by a low pain threshold and a permanent state of pain. The mechanisms explaining this complex disorder remain unclear, and its genetic factors have not yet been identified. With the aim of elucidating FM genetic susceptibility factors, we selected 313 FM cases having low comorbidities, and we genotyped them on the Illumina 1 million duo array. Genotypic data from 220 control women (Illumina 610k array) was obtained for genome-wide association scan (GWAS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 45 publications
2
44
0
3
Order By: Relevance
“…Several approaches have been adopted to circumvent this problem, including the use of a dedicated candidate gene platform that genotypes>3,000 SNPs in >350 gene [473], the study of genome-wide associations in CWP [474] and FMS [475], and whole exome sequencing with various filters [476]. These failed to confirm any of the associations previously reported in candidate gene studies, and each identified only one or a few genes as showing associations with CWP or FMS, but these genes all differed between studies.…”
Section: Potential Pathogenetic Mechanisms Genetics and Epigeneticsmentioning
confidence: 99%
“…Several approaches have been adopted to circumvent this problem, including the use of a dedicated candidate gene platform that genotypes>3,000 SNPs in >350 gene [473], the study of genome-wide associations in CWP [474] and FMS [475], and whole exome sequencing with various filters [476]. These failed to confirm any of the associations previously reported in candidate gene studies, and each identified only one or a few genes as showing associations with CWP or FMS, but these genes all differed between studies.…”
Section: Potential Pathogenetic Mechanisms Genetics and Epigeneticsmentioning
confidence: 99%
“…A second study utilizing GWAS for the study of FMS has recently been published [70]. In this study, Docampo et al performed both GWAS analysis and copy number variant (CNV) analysis by array comparative genomic hybridization (aCGH).…”
Section: Genome-wide Association Studiesmentioning
confidence: 99%
“…8,58 Over the last decade, several candidate genes have been identified that are potentially linked to CWP 31,45,47 , however, only a few of these genes have been reliably replicated. Agnostic approaches such as at genome-wide linkage and association have produced some novel findings 13,16 but together they explain only a fraction of the genetic contribution.…”
Section: Introductionmentioning
confidence: 99%